The effect of hyoid suspension in a multilevel surgery concept for obstructive sleep apnea - Baisch, Alexander; Maurer, Joachim T.; Hörmann, Karl (Otolaryngology - head and neck surgery, 2006)
OBJECTIVE: This study investigated the outcome of the hyoid suspension as a part of a multilevel surgery protocol., STUDY DESIGN AND SETTING: Eighty-three patients with obstructive sleep apnea (OSA) underwent a multilevel surgical treatment because of continuous positive-airway pressure intolerance, 67 with the hyoid suspension and 16 without the hyoid suspension. All patients underwent a pre- and postoperative polysomnography in the sleep laboratory., RESULTS: The mean preoperative apnea hypopnea index (AHI) was 36.4 ± 21.2 and 19.4 ± 19.7 postoperatively for all patients (P < 0.0001). Further statistically significant changes were found for the arousal index, the oxygen saturation, and the daytime sleepiness. No statistically significant change was found for body mass index. In the group of patients treated without the hyoid suspension, the AHI did not decrease statistically significant. After surgery, 59.7% of the subjects with the hyoid suspension were regarded as cured., CONCLUSION: Multilevel surgery including the hyoid suspension is an effective treatment in subgroup of OSA patients., EBM rating: C-4